2014
DOI: 10.1111/evj.12245
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, Ki67, EcPV2‐ and EcPV3 DNA, and viral genes in relation to metastasis and outcome in equine penile and preputial squamous cell carcinoma

Abstract: In equine penile and preputial SCC, tumour grading is an important prognosticator for survival and a predictor for presence of metastases. Expression of p53 and Ki67 and presence or expression of EcPV2 and EcPV3 do not appear to be important prognosticators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 29 publications
4
39
2
5
Order By: Relevance
“…4 In horses, oncogenic E6 transcript from EcPV2 was detected by reverse transcriptase PCR in genital SCCs, which suggests an active pathogenic role of the virus. 13,15 Nonetheless, because the virus replicates in surface epithelium, these techniques by themselves cannot demonstrate causality because they do not provide information on the distribution of expression within the tumor. Several studies have convincingly used oligomer in situ hybridization (ISH) to demonstrate that EcPV2 DNA is present within nuclei of a subset of tumor cells.…”
mentioning
confidence: 99%
“…4 In horses, oncogenic E6 transcript from EcPV2 was detected by reverse transcriptase PCR in genital SCCs, which suggests an active pathogenic role of the virus. 13,15 Nonetheless, because the virus replicates in surface epithelium, these techniques by themselves cannot demonstrate causality because they do not provide information on the distribution of expression within the tumor. Several studies have convincingly used oligomer in situ hybridization (ISH) to demonstrate that EcPV2 DNA is present within nuclei of a subset of tumor cells.…”
mentioning
confidence: 99%
“…Penile and preputial SCC mainly affects older horses and most studies report an average age of 17 to 20 years. 17,18 Carcinoma development has been attributed to the presence of bovine papilloma viruses but the relationship between the two conditions has not been definitively established. The virus can be found on normal sin and in particular on areas of inflamed or ulcerated skin in other conditions as well.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…Expression of cell proliferation markers, such as Ki67 and tumour suppressor genes, for example p53, may also be evaluated using immunohistochemical staining of histopathological sections (Van den Top et al . ). Such markers are increasingly used in assessment of numerous types of small animal neoplasms such as canine mast cell tumours (Webster et al .…”
Section: Introductionmentioning
confidence: 97%
“…A positive correlation between high grade SCCs and metastasis has been demonstrated and it has also been shown that tumour grading is an important prognosticator for survival in horses (van den Top et al . , ). This information, in conjunction with a published classification system (Van den Top et al .…”
Section: Introductionmentioning
confidence: 99%